AN INVESTIGATION OF ORAL READING FLUENCY OF TENTH GRADE IN ONE OF SENIOR HIGH SCHOOLS IN INDRAMAYU - Indra Yoga Prawiro; Sri - Lefina (Universitas Muhammadiyah Tangerang, 2021)
The purpose of this study is to investigate students oral reading fluency of tenth grade in one of Senior High Schools in Indramayu. According to Zuhra (2015) the students faced difficulties in English because of their poor vocabulary. The students also faced difficulties when the texts were long and complicated with various different modifying phrases. There are three subskills to measure oral reading fluency. As stated by Pey, et al (2014) there are ‘accuracy’. ‘speed’, and ‘prosody’. Case study is chosen as a research method in this study. Two instruments were used to collect the data. The first is oral reading fluency test, this was used to measure students’ fluency in oral reading. The second is questionnaire. It was used to find out the students’ reading interest and reading habit. After the writers got the data. Then it will be analyzed qualitatively. The results showed that there were 36 students who took the oral reading fluency test. But, unfortunately that almost all students were not fluent in oral reading. The lowest score obtained by students in reading rate is 58 wpm. While for reading accuracy the lowest score obtained by students is 0,7 wc. And the lowest score obtained by students in reading prosody is 4. In reading prosody, almost all students get score of 4. It is because there are still many students who read only if they have to and they read not for own pleasure. Meanwhile, only two students out of thirty-six students who are almost fluent reading are able to do oral reading fluency. Have fluency in oral reading the students have practiced reading a lot. With reading rate 110 wpm and 127 wpm, reading accuracy 0,95 wc and 0,91 wc, and reading prosody are 9 of out 16.